2012
DOI: 10.1021/jp306030b
|View full text |Cite
|
Sign up to set email alerts
|

Response of Rotation–Translation Blocked Proteins Using Langevin Dynamics on a Locally Harmonic Landscape

Abstract: Langevin dynamics is used to compute the time evolution of the nonequilibrium motion of the atomic coordinates of a protein in response to ligand dissociation. The protein potential energy surface (PES) is approximated by a harmonic basin about the minimum of the unliganded state. Upon ligand dissociation, the protein undergoes relaxation from the bound to the unbound state. A coarse graining scheme based on rotation translation blocks (RTB) is applied to the relaxation of the two domain iron transport protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
25
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(25 citation statements)
references
References 21 publications
0
25
0
Order By: Relevance
“…Recently, there has been renewed interest in using linear response theory (LRT) (2,(6)(7)(8)(9) to describe such ligand-triggered motions. In the framework of LRT, observed conformational changes result from a delicate interplay between protein intrinsic dynamics and the external perturbations that excite the most relevant global modes (2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, there has been renewed interest in using linear response theory (LRT) (2,(6)(7)(8)(9) to describe such ligand-triggered motions. In the framework of LRT, observed conformational changes result from a delicate interplay between protein intrinsic dynamics and the external perturbations that excite the most relevant global modes (2).…”
Section: Introductionmentioning
confidence: 99%
“…The Coalson group also derived a time-dependent version of the theory to characterize fine-and coarse-grained presentations of the ligand binding process on timescales of hundreds of picoseconds or longer (6,7). The authors also showed that the exaggerated curvature might be overcome by quasiharmonic approximation of the roughness of the energy landscape caused by anharmonicity (7).…”
Section: Introductionmentioning
confidence: 99%
“…Even though this suggests that these structures are rigid, it does not mean that they will necessarily remain rigid under an arbitrary applied force. In a previous paper, 10 we attempted to model rigid units and to incorporate these units into the dynamics of the system. We found that even though the motions were qualitatively similar to those of the all-atom control (i.e., the same system with no rigidity constraints imposed), the potential energy surface (PES) was steeper than the all-atom control so the relaxations of the Langevin modes were faster.…”
mentioning
confidence: 99%
“…In our previous study of rigid block dynamics, 10 which did not allow for internal distortions within a block, we suggested two ways to rectify the problems associated with purely rigid blocking. One way is to add back a subset of the suppressed internal (vibrational) degrees of freedom in each block to the six rotation-translation block (RTB) degrees of freedom (dof's).…”
mentioning
confidence: 99%
See 1 more Smart Citation